The Effect of Company Size, Company Age, Public Ownership and Audit Quality on Internet Financial Reporting - Maulida Dewi Firdaus Abdullah; Muhammad Noor Ardiansah; Nurul Hamidah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study aims to examine the effect of company size, company age, public ownership, and audit quality toward Internet financial reporting on companies listed in Indonesia Sharia Stock Index (ISSI). This study uses secondary data from the financial statements issued by each company for the period 2015 and a report published by the Indonesia Stock Exchange (IDX). Logistic regression analysis model is used to analyze the data. The result of the research shows that IFR is influenced positively and significantly by company size, company age and public ownership indicating that the higher company size, company age and public ownership of a company, the higher the company's opportunity to do IFR. Meanwhile, IFR is influenced positively but not significant by audit quality, this because there are 60 companies that audited by non big ten accounting firms but doing IFR and there are 12 companies that audited by big ten accounting firms but not doing IFR. The influence of the four variables on IFR is 67,8%.